The Reception of the Musical and Liturgical Reform of the Second Vatican Council in the Diocese of Opole: Between Tradition and Modernity - Świecarz, Grzegorz (Roczniki Kulturoznawcze, 2024)
The article analyzes the reception of the musical and liturgical reform of the Second Vatican Council in the Diocese of Opole, with particular focus on the adaptation of conciliar guidelines within the context of local cultural and religious conditions. The process of implementing the reform was complex, involving both official actions by Church institutions and grassroots initiatives by sacred music creators. Key roles were played by local musicians, composers, and educators, such as Alfred Bączkowicz, Józef Chudalla, and Fr. Grzegorz Poźniak, whose dedication contributed to the development of a new musical repertoire that harmoniously blended tradition with modernity. The article details the reception process, highlighting how educational, formative, and editorial efforts strengthened the role of music in liturgy and preserved its heritage. The findings suggest that the reception of the reform remains a dynamic process, and liturgical music plays a crucial role in integrating the faithful with the liturgy while maintaining the Church's traditions in the Diocese of Opole.